Local Government Supervision of Overseas Labor Supply Companies (Case Study In Cirebon Regency) - Dudung Hidayat; Deni Yusup Permana; Rd. Handriono; Andasmara Rizky Pranata; Karmenita Karmenita; Nur Rahmat (Asian Journal of Social and Humanities, 2024)
Crucial issues related to the protection and supervision of Indonesian migrant workers (PMI) working abroad. In the context of the Indonesian economy, PMI has an important role in generating economic contributions to the country and providing economic benefits for their families in Indonesia. Constitutional foundations, such as Article 27 paragraph (2) and Article 28D paragraph (2) of the 1945 Constitution, as well as the Indonesian Migrant Manpower Law No. 18 of 2017, have provided a clear legal framework on the obligations of local governments in regulating, fostering, implementing, and protecting the rights of migrant workers. However, there are still obstacles and violations that often occur in sending workers abroad, such as unsettled wage payments and contract problems. This study aims to analyze local government supervision of labor supply companies in Cirebon Regency and identify common violations in sending workers abroad along with the necessary solutions. The research findings highlight the importance of increased supervision, stricter law enforcement, and cross-border collaboration to protect and improve migrant workers' working conditions, and make it the basis for recommending further measures for the welfare of Indonesian migrant workers.